2020
DOI: 10.1002/jsde.12444
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Behavior of Synthesized Liquid Soaps and Surface Activity Properties of Surfactants

Abstract: In the present work, a rheological study of liquid soaps prepared from different mixture of surfactants as a function of surfactant type and concentration was performed. The curves of shear stress vs. shear rate and viscosity vs. shear rate were recorded at constant temperature, 294 ± 0.1 K. The surface activity properties were also studied. The results of the study showed that values of surface tension, γ, were in the range 31-40 mN m −1 and the critical micelle concentration (CMC), was of the order 10 −4 mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This results indicated, the particles of gold insert to bubble of foam in hand soap by physics interaction. Furthermore, we reported the pH of hand soap@G-NPs was 6.0 that the according with Indonesian National Standard (SNI) [28][29]. From this results, can be concluded the G-NPs to function at the foam height stability in liquid hand soap formulations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This results indicated, the particles of gold insert to bubble of foam in hand soap by physics interaction. Furthermore, we reported the pH of hand soap@G-NPs was 6.0 that the according with Indonesian National Standard (SNI) [28][29]. From this results, can be concluded the G-NPs to function at the foam height stability in liquid hand soap formulations.…”
Section: Discussionmentioning
confidence: 65%
“…Hand soap is included in personal care liquid products that are widely produced because it is more practical and has an attractive shape compared to solid soap. The parameters test such as viscosity, pH, the color of liquid soap, and foam stability produced after the formulation process greatly affect the physical properties of hand soap products [26][27][28][29][30][31]. Some previous research reported, the color agent for hand soap products uses congo red, methyl orange, and methylene blue.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted SDS can produce a short‐lived foam (Bois et al, 2020), which collapsed within 15 min. The interaction between anionic surfactant (SDS) and nonionic co‐solvent (glycerol) increased the viscoelasticity (Bratovcic and Nazdrajic, 2020) of the soap solution and maintained the soap bubble for more than 15 min. It can be seen that the tension remains constant throughout the bubble's lifetime, showing fast adsorption of the surfactant molecules at the air/water interface (Nguyen et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, flocculation occurs at SBNS concentrations above the CMC to impair the surface activity of the surfactant. , This reflects the imperativeness to determine the CMC during any surfactant flooding operation. The CMC of SBNSs depends on factors such as its molecular structure (e.g., hydrophobic chain length), solution salinity, pressure conditions, ionic composition, pH, temperature, and others …”
Section: Characterization Of Sbnssmentioning
confidence: 99%
“…71,103 This reflects the imperativeness to determine the CMC during any surfactant flooding operation. The CMC of SBNSs depends on factors such as its molecular structure (e.g., hydrophobic chain length), 121 solution salinity, 122 pressure conditions, 123 ionic composition, pH, temperature, and others. 124 As a rule of thumb, the amount of surfactant concentration for injection in CEOR processes is assumed to be two or three times the CMC value.…”
Section: Critical Micelle Concentrationmentioning
confidence: 99%